2012
DOI: 10.1007/s10953-012-9851-2
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Excess Molar Volumes of Alkane (Heptane, Octane, Nonane, or Decane) + Thiophene from T=293.15 to 313.15 K

Abstract: Densities of four binary systems composed of an alkane (heptane, octane, nonane, or decane) and thiophene were measured at temperatures from 293.15 to 313.15 K at atmospheric pressure (0.7 atm). Measurements were made covering the full range of compositions for all systems studied and for the pure compounds by using a vibrating-tube densimeter (VTD). Excess molar volumes have been obtained from these experimental results and were fitted to a Redlich-Kister type expansion. The excess molar volumes exhibit posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… a Standard uncertainty in the density measurement = 3·10 –2 kg·m –3 , standard uncertainty in the surface tension = 0.03 mN·m –1 , and standard uncertainty in the temperature measurement = 0.01 K. a Reference . b Reference . c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . k Reference . l Reference . m Reference . n Reference . o Reference . p Reference . q Reference . r Reference . s Reference . t Reference . u Reference . v Reference . w Reference . x Reference . y Reference . z Reference . aa Reference . ab Reference . ac Reference . ad Reference . ae Reference . af Reference . ag Reference . ah Reference . ai Reference . aj Reference . …”
Section: Methodsmentioning
confidence: 99%
“… a Standard uncertainty in the density measurement = 3·10 –2 kg·m –3 , standard uncertainty in the surface tension = 0.03 mN·m –1 , and standard uncertainty in the temperature measurement = 0.01 K. a Reference . b Reference . c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . k Reference . l Reference . m Reference . n Reference . o Reference . p Reference . q Reference . r Reference . s Reference . t Reference . u Reference . v Reference . w Reference . x Reference . y Reference . z Reference . aa Reference . ab Reference . ac Reference . ad Reference . ae Reference . af Reference . ag Reference . ah Reference . ai Reference . aj Reference . …”
Section: Methodsmentioning
confidence: 99%
“…The experimental values of densities, viscosities, and refractive indices of the pure samples under different temperatures are compared with those from the references ,, in Table . The absolute average relative deviations (AARD) are calculated according to the following equation, and the results indicate that the experimental values agree well with the literature data. where P is the measurement data of density, viscosity, or refractive index in this work, and P lit is the literature data.…”
Section: Resultsmentioning
confidence: 99%
“… a Standard uncertainties u are u ( p ) = 0.50 kPa, u ( T ) = 0.01 K, u r (ρ) = 0.001, u r (η) = 0.02, and u c ( n D ) = 0.0005. b Ref . c Ref . d Ref . e Ref . f Ref . g Ref . h Ref . i Ref . j Ref . k Ref . l Ref . m Ref . n Ref . o Ref . p Ref . q Ref . r Ref . …”
Section: Resultsmentioning
confidence: 99%
“…In the binary solutions of (thiophene + cyclohexane/hexane), the density d values for the solutions containing cyclohexane are greater than the solutions containing hexane. The densities of binary systems {x (heptane, octane, nonane, or decane) + (1 À x) (thiophene)} have been measured at T = (293.15 to 313.15) K and it was found that the density values increase in the presence of thiophene [26].…”
Section: Volumetric Propertiesmentioning
confidence: 99%